Morphofunctional State Of Adrenal Blood Vessels In Experimental Rat Thyrotoxicosis - Ilyasov Aziz Saidmuratovich; Umarkulova Gulbakhor Alisherovna (Genius Journals, 2024)
In the bloodstream of the adrenal glands of rats, a number of anatomical and histostructural features of the structure of the terminal part of the hemomicrocirculatory bed in the form of a three-dimensional spatial capillary network are noted, which indicates the organ specificity of this component of the hemocirculation system in the adrenal glands. Changes in the organization of the hemomicrocirculatory bed are directly related to any morphofunctional transformations in the adrenal glands, reflecting the mechanisms of adaptation and compensation.Experimental thyrotoxicosis in rats revealed an increase in the diameter of venules and capillaries to 20.0% in the cortical zone, arterioles to 17.0% in the cerebral zone. The thickness of the microvascular wall decreases by 25.0% of the arteriole of the cerebral zone
Keywords: rats; adrenal glands; capillaries